A mucoadhesive gingival patch with Epigallocatechin-3-gallate green tea (Camellia sinensis) as an alternative adjunct therapy for periodontal disease: A narrative review - Yeka Ramadhani; Riski Rahayu Putri Rahmasari; Kinanti Nasywa Prajnasari; Moh. Malik Alhakim; Mohammed Aljunaid; Hesham Mohammed Al-Sharani; T. Tantiana; Wisnu Setyari Juliastuti; Rini Devijanti Ridwan; Indeswati Diyatri (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: Periodontitis is a progressive destructive periodontal disease. The prevalence of periodontal disease in Indonesia reaches 74.1% and mostly occurs in the productive age group. Most of the periodontopathogenic bacteria are gram-negative bacteria and have endotoxin in the form of lipopolysaccharide (LPS), which can penetrate the periodontal tissue and induce an inflammatory response. In inflammatory conditions, osteoclastic activity is higher than osteoblastic activity, which causes bone destruction. This results in an imbalance between osteoclast-induced bone resorption and osteoblast-induced bone formation. The current preferred treatment for periodontitis is scaling root planning (SRP), but this therapy cannot repair the damaged periodontal tissue caused by periodontitis. Purpose: To describe the possibility of using a mucoadhesive gingival patch with Epigallocatechin-3-gallate (EGCG) green tea (Camellia sinensis) as alternative adjunct therapy for periodontal disease. Review: EGCG is the main component of green tea catechins, which have antitumor, antioxidant, anti-inflammatory, anti-fibrotic, and pro-osteogenic effects. However, the weaknesses so far regarding the use of EGCG as an alternative treatment is its low oral bioavailability and the concentration of EGCG absorbed by the body decreasing when accompanied by food. EGCG can be used with a mucoadhesive gingival patch to optimise bioavailability and absorption and increase local concentration and sustained release of EGCG. EGCG encourages bone development and braces mesenchymal stem cells (MSCs) differentiation for osteoblast by enhancing the expression of bone morphogenic protein 2 (BMP2). EGCG also has been proven to increase the expression of RUNX2 and ALP activity that induces osteoblast differentiation and bone mineralisation. Conclusion: A mucoadhesive gingival patch containing EGCG Green Tea (C. sinensis) may potentially induce osteoblastic activity as an adjunct therapy to repair the periodontal tissue damage due to periodontal disease.